Acceptance Model for Family Planning Program in Baduy’s Remote Indigenous Community in Leuwidamar District, Lebak Banten - Dimyati, Idi; Sihabudin, Ahmad; Tobing, Melati Mediana (International Journal of Social and Management Studies, 2022)
In the beginning, Baduy’s Remote Indigenous Community (KAT Baduy) received the family planning program, they were generally using implants then changed to pill contraceptives. Currently, almost all family planning acceptors in Baduy use injectable contraception. Based on this phenomenon, this research examined what channels or media play a role in the spread of family planning and how it relates to the effectiveness of their innovation acceptance in the Baduy community. The research method is an explanatory survey using frequency distribution analysis, with Spearman correlation analysis to determine the relationship between variables. The results show all communication channels or reference sources of information from respondents who obtain information about Family Planning (KB). With 200 samples from 1528 family planning acceptors in KAT Baduy (1503 family planning acceptors in Outer Baduy and 25 family planning acceptors in Inner Baduy), most of the respondents received information about family planning from their relatives or neighbors. Only 22% of respondents admitted that health workers or midwives were their sources of family planning information. Posyandu cadres were a source of family planning information for 21% of respondents. Village officials which are customary leaders or kakolot adat are only mentioned by 7% of respondents as a source of family planning information. The remaining 1% have received family planning information from other sources such as friends or the media. The majority of respondents stated that their decision to take family planning or accept the concept of family planning was only about 6 months. In a conclusion, the relationship between the type of communication channel and the effectiveness of innovation acceptance has a positive and "quite strong" relationship. For recommendation, this research suggests to health worker from Cisimeut Health Center keep their internal task of providing health services and assistance to Baduy residents in Kanekes Village, though there are challenges from external parties which builds overlapping and miscoordination health services with several social actions and health volunteers from outside Baduy.